Critical reflections – The Theory of Planned Behaviour: An interview with Icek Ajzen with implications for entrepreneurship research. (August 2019) - Tornikoski, Erno; Maalaoui, Adnane
Research on the formation of entrepreneurial intention has attracted substantial attention and interest from entrepreneurship scholars. In this quest, one theory that has been very popular is the Theory of Planned Behaviour (TPB) by Icek Ajzen. Professor Ajzen was one of the first to study intentions and behaviour, particularly with Fishbein, from the end of the 1960s. Since its inception, TPB has tested, advanced and challenged in many social science fields and, as a result, generated substantial interest among researchers: The seminal 1991 article by Ajzen has generated alone more than 60, 000 citations to date. For a more in-depth investigation of his TPB model, we had the opportunity to interview Professor Icek Ajzen. This Research Note presents the transcript of the interview before we then synthesise some of the key ramifications of the interview for research on entrepreneurial intention.